Is ChatGPT Woke? Comparative analysis of '1984' and 'Brave new world' in the Digital Age - Polo Serrano, David (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
A study that examines the application of 'woke' ideology in the generation of textual content with ChatGPT, comparing the premises of the dystopias '1984' and 'Brave New World' with the outcomes produced by the AI. Through a participatory methodology with university students, the bias present in ChatGPT related to 'wokeness' is explored. The practical results show parallels with ideological control and the supposed freedom and equality, discussing the role of AI in amplifying social movements, while also highlighting the intersection between technology and social change in the information age.